Environmental Disclosure on Biodiversity Dimension: Does Media Exposure Matter ? - Aji, Nur Prasetyo; A’zizah, Laila Oshiana Fitria; Azzahra, Ainun Fadila; S, Nurlita Arum (Universitas Muhammadiyah Sorong, 2025)
This study aims to examine the influence of media exposure in regulating the relationship between foreign ownership, institutional ownership, and environmental performance on biodiversity disclosure. The study uses secondary data obtained from sustainability and annual reports of manufacturing companies listed on the Indonesia Stock Exchange during the 2020–2022 period, selected using a purposive sampling method. A quantitative approach is applied using multiple regression analysis, specifically Moderated Regression Analysis (MRA), to test the moderating effect of media exposure. The findings indicate that environmental performance positively affects biodiversity disclosure, and media exposure plays a role in moderating this relationship. However, the measurement of media exposure remains general and does not differentiate between positive and negative news tone. This study provides empirical evidence from Indonesia that highlights the relevance of media exposure and environmental performance in improving biodiversity disclosure practices among corporations.